Microstructure, Mössbauer, and Optical Characterizations of Nanocrystalline α-Fe2O3 Synthesized by Chemical Route. (12th October 2011) - Banerjee, Abhijit; Patra, Soumitra; Chakrabarti, Mahuya; Sanyal, Dirtha; Pal, Mrinal; Pradhan, Swapan Kumar
Abstract : Nanocrystalline α -Fe2 O3 of crystallite sizes ranging from 18 nm to 54 nm has been prepared by sol gel process and postannealing the powder up to 500C ∘ . X-ray diffraction and transmission electron microscopy images have been used for determining the average crystallite sizes of the prepared samples. The Rietveld analysis reveals that the "as-prepared" α -Fe2 O3 powders are not completely stoichiometric, and significant ( 20%) oxygen vacancies are noticed in the α -Fe2 O3 lattice. Oxygen atoms in as-prepared sample are significantly displaced and the lattice is heavily distorted. With increasing annealing temperature the lattice approaches towards the stoichiometric oxygen concentration and perfect lattice configuration. Mössbauer spectrum of the unannealed (as-prepared) α -Fe2 O3 sample shows the superparamagnetic behavior at room temperature whereas all annealed samples show complete ferromagnetic behavior. Optical band gaps of these nanocrystalline α -Fe2 O3 samples have been measured from UV-Vis spectroscopy and found to decrease from 2.65 eV to 2.50 eV, like an n-type semiconductor, with increasing annealing temperature up to 500C ∘ .